Inhaled Remimazolam Potentiates Inhaled Remifentanil in Rodents. (May 2017) - Bevans, Tatjana; Deering-Rice, Cassandra; Stockmann, Chris; Rower, Joseph; Sakata, Derek; Reilly, Christopher
Abstract : BACKGROUND: Remimazolam is an ester-based short-acting benzodiazepine currently in clinical trials for IV administration. This study explored the feasibility of delivering remimazolam alone and as an adjunct to remifentanil via inhalation in rodent models. METHODS: Mice were exposed to remimazolam via inhalation; sedation was assessed using time to movement outside a set perimeter. Rats were also exposed to remimazolam aerosol alone and in combination with inhaled remifentanil, and analgesia was quantified by using a tail flick meter. Pulmonary injury was assessed in mice using mechanics measurements. RESULTS: Mice showed significantly increased time to movement outside a set perimeter after 5-minute exposure to increasing concentrations (10–25 mg/mL solutions) of inhaled remimazolam aerosols. Differences in mean (95% confidence interval) time to movement from pretest baseline group (0.05 [0.01–0.09] minutes) were 11 (4–18), 15 (5–26), 30 (19–41), and 109 (103–115) minutes after exposure to remimazolam aerosol of 10, 15, 20, and 25 mg/mL, respectively ( P = .007 – P < .0001). Exposure of rats to remimazolam aerosols alone failed to produce sedation or analgesia after a 5-minute exposure. When remimazolam (10 or 25 mg/mL) was administered in combination with 250 μg/mL remifentanil, there was a significant difference in time to tail flick ( P < .0001) consistent with a strong analgesic effect. Mean (95% confidence interval) differences in time to tail flick from the pretest baseline group (3.2 [2.5–3.9] seconds) were 14 (10–18) seconds when 250 μg/mL remifentanil was administered with either 10 or 25 mg/mL remimazolam. Remimazolam alone or in combination with remifentanil did not cause lung irritation, bronchospasm, or other adverse pulmonary events to the respiratory tract of mice as assessed by Flexi-Vent pulmonary function tests. CONCLUSIONS: Remimazolam can significantly potentiate the analgesic effect of remifentanil when concurrently delivered via inhalation.